2017
DOI: 10.4102/ajlm.v6i1.578
|View full text |Cite
|
Sign up to set email alerts
|

National laboratory policies and plans in sub-Saharan African countries: gaps and opportunities

Abstract: IntroductionLaboratory services are key to the quality of healthcare but have remained a historicallyneglected component of health systems in low-and middle-income countries. The need for quality medical laboratory services to form an integrated part of the health system has been widely acknowledged by key national and international players during the past decade, resulting in the mobilisation of substantial funding earmarked for laboratory improvement in resource-limited settings. 1,2 Alongside these efforts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Special focus is needed to identify funding for cancer medicines that offer substantial and clinically meaningful benefit. Moreover, availability of diagnostic platform systems such as radiology and pathology are severely limited across Africa [22] and require increased capacity to meet the population needs. Recent global data also describe the association between high clinical volumes and low job satisfaction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Special focus is needed to identify funding for cancer medicines that offer substantial and clinically meaningful benefit. Moreover, availability of diagnostic platform systems such as radiology and pathology are severely limited across Africa [22] and require increased capacity to meet the population needs. Recent global data also describe the association between high clinical volumes and low job satisfaction [23].…”
Section: Discussionmentioning
confidence: 99%
“…Integrated POC testing to include recommended clinical chemistry or hematology tests may be important to further improve HIV treatment services (229). Simple POC hemoglobin assays are becoming more widespread in primary care services and can be used for the monitoring PLHIV receiving zidovudine.…”
Section: Additional Diagnostics Needed For Hiv Monitoringmentioning
confidence: 99%
“…Respondents to the laboratory system strengthening course questionnaires, reported that they contributed to developing the country’s first National Laboratory Strategic Plan, Supply Chain Management Systems or Laboratory Information Systems plans (Table 3 ). We are delighted to see that with training ACILT provided alongside in-country assistance as of January 2017, 39 countries developed or were in the process of developing their National Laboratory Strategic Plans [ 37 ]. However, lack of financial resources to advocate for National Laboratory Strategic plan for 14 respondents was also noticed.…”
Section: Discussionmentioning
confidence: 99%